Identifikasi Desa Sebagai “Lewu Proklim” di Kabupaten Pulang Pisau - Hukom, Alexandra (Jurnal Green Growth dan Manajemen Lingkungan, 2023)
Pro-Climate Village is a government program to increase community involvement in adaptation and mitigation of environmental change and reduction of greenhouse gas emissions. This study aims to identify villages along the trans Kalimantan road and on the banks of the Kahayan river. By using descriptive analysis and SWOT analysis it was found that Pilang Village based on the Proklim Program Guidelines could be used as Lewu Proklim. The results of the analysis show that strengthening the intensive socialization strategy to introduce the climate village program to the community. Adaptation by adding irrigation canals, collecting rainwater and developing demonstration gardens that have been used as orangutan food in the Orangutan Release Conservation. Mitigation by accustoming the community to using organic fertilizers and promoting tree planting activities in an incentive manner, especially on the shores of the Kahayan River. Participation by utilizing community leaders as role models and holding traditional ritual events to establish communication between residents and cultural and religious approaches.